Cystic fibrosis-related education: Are we meeting patient and caregiver expectations?. Issue 10 (October 2018) - Lonabaugh, Kevin P.; O'Neal, Katherine S.; McIntosh, Heather; Condren, Michelle
Highlights: Cystic fibrosis (CF) patients report confidence in knowledge related to nutrition. Participants report reproductive effects of CF as not often being discussed. Clinic providers are the number one source of information. Many patients and caregivers also use the Internet for information about CF. Educational goals are expected to be met by the early teen years. Abstract: Objective: The purpose of this study was to improve patient education in clinic by evaluating patient perceptions of education provided, as well as patient self-confidence related to topics within cystic fibrosis (CF). The study assessed whether self-confidence matched knowledge and defined patient-specific goals for education timing and information sources. Methods: Age specific questionnaires were distributed over four months to patients 11 years of age and older and caregivers of patients of all ages at a single CF Foundation accredited care center. Results: Participants reported frequent education on all topics except for reproductive effects of CF and mental health. A positive correlation was seen between overall confidence in CF-related knowledge and performance on a validated knowledge scale in adolescent caregivers only. Participants expected all educational milestones to be met by 13–14 years of age. Conclusions: Gaps in CF education remain and educational models should deliver information by the early teens without overlooking reproductive effects and mental health. Practice Implications: The educational model for CF clinics should become more comprehensive by including education on topics such as mental health and reproductive effects. Providers are an important pathway for information and should not disregard the value of education provided during clinic visits.